2022-RA-1604-ESGO Efficiency of simulation program for OB/GYN residents using self-training and supervised sessions: a quantitative study. (20th October 2022) - Aissaoui, Othman; Titaux, Cyrielle; Delporte, Victoire; Kerbage, Yohan; Rubod, Chrystele; Hudry, Delphine
Abstract : Introduction/Background: The objective of this study was to evaluate the progress of OB/GYN residents on surgical exercises on simulating laparoscopic surgery, and satisfaction with this program. Methodology: A prospective study evaluating the technical level of OB/GYN residents on box-trainer. Two groups were formed: a 'beginner' group, in their 2nd year of residency and an 'advanced' group corresponding to residents in their 4th year. Twice a year, each student is evaluated and timed on the completion of 4 exercises during a supervised session. The material was left at the students' disposal for self-learning practice on a voluntary basis. The variables retained were the time required to validate the exercise, and the completeness of the achievement. Student satisfaction and interest were then assessed by following an anonymous online questionnaire. Results: Between November 2019 and March 2021, 25 students were enrolled in the study. 69% in beginner group and 50% in advanced group completed at least one self-training session between the two evaluations. For the two groups, there was a significant improvement in the time taken to complete the exercises between the last and the first supervised session (p<0.005 for all exercises). Students who had done more than one self-training session had improved their score, more importantly, but not significantly, compared to students without self-training sessions. The majority, 96%, was satisfied with the realism of the exercises on box-trainer. All of them were in favor of its introduction in their curriculum and 83% attest that these training sessions have improved their confidence during laparoscopic procedures. Conclusion: This study confirms the interest of laparoscopic training programs integrating simulation on the execution of surgical gestures. The residents are interested in a program combining self-training sessions with supervised sessions. Integrating all of these sessions into the OB/GYN residents' schedule is one of the future challenges.